2016
DOI: 10.1111/cobi.12711
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of aceclofenac in cattle to vulture‐killing diclofenac

Abstract: The non-steroidal anti-inflammatory drug (NSAID) diclofenac is highly toxic to Gyps vultures and its recent widespread use in South Asia caused catastrophic declines in at least three scavenging raptors. The manufacture of veterinary formulations of diclofenac has since been banned across the region with mixed success. However, at least 12 other NSAIDs are available for veterinary use in South Asia. Aceclofenac is one of these compounds and it is known to metabolise into diclofenac in some mammal species. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…In addition to the continuing threat from diclofenac, other veterinary NSAIDs that are toxic to Gyps vultures are approved for legal use in India and are likely to be causing mortality. These include ketoprofen, for which there is experimental evidence of toxicity to vultures below the maximum level of exposure for White-rumped Vulture (Naidoo et al 2010) and aceclofenac, which is largely metabolised to diclofenac within cattle (Galligan et al 2016). In addition, nimesulide residues have been found associated with visceral gout in vultures found dead in the wild in India (Cuthbert et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the continuing threat from diclofenac, other veterinary NSAIDs that are toxic to Gyps vultures are approved for legal use in India and are likely to be causing mortality. These include ketoprofen, for which there is experimental evidence of toxicity to vultures below the maximum level of exposure for White-rumped Vulture (Naidoo et al 2010) and aceclofenac, which is largely metabolised to diclofenac within cattle (Galligan et al 2016). In addition, nimesulide residues have been found associated with visceral gout in vultures found dead in the wild in India (Cuthbert et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, diclofenac formulated for human use continues to be used illegally and several other veterinary drugs (e.g. ketoprofen, aceclofenac, nimesulide) available for legal use are known to be nephrotoxic to be vultures (Cuthbert et al, 2016;Galligan et al, 2016;Naidoo et al, 2010). Hence, understanding the contribution of domestic livestock in the diet of vultures could still serve as an important index of mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, safety trials have now confirmed nephrotoxicity at plausible field exposure levels in Gyps due to ketoprofen [33], carprofen [34] and aceclofenac [35] -whilst very worryingly, both nimesulide (in South Asia; [36] and flunixin (in Europe; [37]) have now been clearly linked to wild Gyps mortalities on two continents. Further, concern now also exists regarding potential impacts on what some may consider to be more enigmatic species such as eagles, following the death of two steppe eagles (Aquila nipalensis) in India in association…”
Section: Accepted Manuscriptmentioning
confidence: 99%